On restriction optimal fixpoints - Vahan K. Margaryan (Изд-во НАН РА)
Optimal ¯xpoints extract maximum consistent information from recursive programs. However, optimal ¯xpoints, although they always exist for a recursive operator, aren't necessarily computable. We have introduced a modi¯ed notion of the optimal ¯xpoint, where the recursive operators are restricted to computable inputs. Existence results for and properties of this ¯xpoint are summarized in the article.
Keywords: Mathematics